2018
DOI: 10.1159/000495897
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons: Distinct Biological Activities and Current Applications for Viral Infection

Abstract: The interferons (IFNs) are a primary defense against pathogens because of the strong antiviral activities they induce. IFNs can be classified into three groups: type I, type II and type III, according to their genetic, structural, and functional characteristics and their receptors on the cell surface. The type I IFNs are the largest group and include IFN-α, IFN-β, IFN-ε, IFN-ω, IFN-κ, IFN-δ, IFN-τ and IFN-ζ. The use of IFNs for the treatment of viral infectious diseases on their antiviral activity may become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 153 publications
4
116
0
2
Order By: Relevance
“…Type I interferon (IFN-I) is a key component of the innate antiviral response, and constitutes the first line of host defence against influenza virus infection [41][42][43] . The activation of the IFN-I response requires PACT, which interacts with RNA polymerase, and nonstructural proteins NS1 and NS2 of influenza A virus 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferon (IFN-I) is a key component of the innate antiviral response, and constitutes the first line of host defence against influenza virus infection [41][42][43] . The activation of the IFN-I response requires PACT, which interacts with RNA polymerase, and nonstructural proteins NS1 and NS2 of influenza A virus 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Upon infection, Influenza virus triggers the innate immune response in host cells to produce Type I interferons (IFNs), which in turn inhibit viral replication. Hence, IFN could be used as a therapy choice for influenza [22]. In our current work, IFNβ treatment activated ACE2 expression in primary human bronchial epithelial cells, suggesting that the host response of ACE2 upregulation is associated with the IFN signaling pathway.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies on the antiviral activity of lopinavir against MERS-CoV are conflicting with one study reporting micromolar EC 50 values in a human hepatoma cell line (Huh 7) yet another reported that lopinavir had no activity in a non-human primate kidney cell line (Vero) de Wilde et al, 2014). Type I interferons are approved for treating multiple indications including hepatitis B and C, and multiple sclerosis (Dumitrescu et al, 2018;Li et al, 2018). Two studies showed interferon-beta was effective against MERS-CoV infection in non-human primate kidney cells (Vero) with EC 50 values < 10 IU/mL Hart et al, 2014).…”
Section: Remdesivir Provides Superior Therapeutic Efficacy To Lopinavmentioning
confidence: 99%